Persepsi dan Partisipasi Masyarakat terhadap Program Pembangunan Hutan Tanaman Rakyat (Studi Kasus Koperasi Rakyat Pantai, Desa Pangkalan Siata, Kecamatan Pangkalan Susu, Kabupaten Langkat) - Yesi Novia O Samosir; Agus Purwoko; Herianto Herianto (Program studi Kehutanan USU, 2015)
Commmunity Plantation Forest is Indonesian government policy which needed participation and responsibility from local community to manage production forest sustainability. Which is expected to make a sustainable and productive forest, increase community welfare through the direct absorption of laborers especially in forestry sector and increase regional economic growth Public be targe to forest plantation development programme in existing can be basis for government policy to empower human so that they will be more active in preserving, managing and using forest potency sustainability. So, the rate of perceptions and public participation on forest plantation programme have to been known. Sampling technique uses purposive sampling. This riset uses primer and secondary data. Primer data can be gotten from survey and direct observation and interview by spread of. Then, counted the rate of perceptions and public participation on forest plantation programme by using formula, then it will be grouped into three categories namely high, medium and low. The result of riset is the level of public perception in Pangkalan Siata Village located in Pangkalan susu district, Langkat is 84,02% (good), the rate of public participation for some acivities such as planning 55,47% (medium), actuating 64,44% (medium), and evaluation 51,10% (medium)Keyword : Public Perception, Public Participation, Commmunity Plantation Forest, Coastal Peoples Cooperation.